The Stability and Growth Pact - Not the best but better than nothing. Reviewing the debate on fiscal policy in Europe's Monetary Union - Martin Heipertz (Max Planck Institute for the Study of Societies, 2003)
This paper aims to review the economic literature on the Maastricht deficit rule and the Stability and Growth Pact. The author tries to expose the contradictions and inconclusiveness of the debate, highlighting both the criticism and the defense of the fiscal policy regime in EMU. The paper is non-technical and seeks to provide an overview for a readership outside the economics profession. The concluding judgment is that the pact can be criticized on a number of grounds, but that the lack of a politically feasible alternative makes it a second best solution that should not be undermined in the present crisis. – – Dieses Papier ist eine summarische Auswertung der wirtschaftswissenschaftlichen Fachliteratur zur Defizitregel des Maastrichter Vertrages und dem Europäischen Stabilitäts- und Wachstumspakt. Der Autor versucht, Widersprüche und fehlenden Konsens der Debatte darzustellen, indem die Argumente für und gegen das fiskalpolitische Regime der Währungsunion einander gegenübergestellt werden. Der Aufsatz ist nicht technisch und dient dem Zugang einer an der Materie interessierten, aber wirtschaftstheoretisch nicht vorgebildeten Leserschaft. Das abschließende Urteil sieht den Pakt als in einer Reihe von Punkten kritikwürdiges Provisorium an, das jedoch mangels einer realisierbaren Alternative nicht ausgehebelt werden sollte.
Keywords: 300